5(u+2)+u=3(u-1)+1

Simplify each term.

Apply the distributive property.

5u+5⋅2+u=3(u-1)+1

Multiply 5 by 2.

5u+10+u=3(u-1)+1

5u+10+u=3(u-1)+1

Add 5u and u.

6u+10=3(u-1)+1

6u+10=3(u-1)+1

Simplify each term.

Apply the distributive property.

6u+10=3u+3⋅-1+1

Multiply 3 by -1.

6u+10=3u-3+1

6u+10=3u-3+1

Add -3 and 1.

6u+10=3u-2

6u+10=3u-2

Subtract 3u from both sides of the equation.

6u+10-3u=-2

Subtract 3u from 6u.

3u+10=-2

3u+10=-2

Subtract 10 from both sides of the equation.

3u=-2-10

Subtract 10 from -2.

3u=-12

3u=-12

Divide each term in 3u=-12 by 3.

3u3=-123

Cancel the common factor of 3.

Cancel the common factor.

3u3=-123

Divide u by 1.

u=-123

u=-123

Divide -12 by 3.

u=-4

u=-4

Solve for u 5(u+2)+u=3(u-1)+1